Sonar sensor for an autonomous mobile robot - Ribuan, Mohamed Najib (2006)
In order to interact with environment, a mobile robot needs an external sensor especially to detect an obstacle along its path to its final destination. A sensor capable to detect any kind of object is very crucial to an autonomous mobile robot and is investigated in this works. The selection of a proper sensor is discussed in this report as well as the development of the sensor in order to achieve the functional sensor system for the application. Moreover, the performance of the constructed sensor is also presented to show the sensor capability on performing the specific task.